2011
DOI: 10.1080/01904167.2011.558160
|View full text |Cite
|
Sign up to set email alerts
|

PHENOLOGY AND SEED QUALITY RESPONSE OF RAPE (B. NAPUS) VERSUS MUSTARD (B. JUNCEA) TO SULFUR AND POTASSIUM FERTILIZATION IN NORTHWEST PAKISTAN

Abstract: 2 Inappropriate sulfur and potassium fertilization, particularly with continued soil nutrient mining and yearly fluctuations in rainfall, are major factors contributing to slow growth and low seed quality of canola in northwestern Pakistan. A field experiment was conducted in 2007 -2008 on a sulfur (S) and potassium (K) deficient clay loam soil under irrigation at the research farm of NWFP (Northwest Frontier Province) Agricultural University, Peshawar, Pakistan, with an objective to determine response of phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The higher rate of N application delayed PM and increased both SPC and TSW but decreased SOC and SSC in maize seeds indicating negative relationship of SPC with SOC and SSC. Earlier in sunflower, In Amanullah et al found that seed protein concentration had negative association with seed oil concentration [30]. The SSC decreased and SPC increased with each increment in N supply indicating negative relationship between SSC and SPC [7].…”
Section: Seed Weightmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher rate of N application delayed PM and increased both SPC and TSW but decreased SOC and SSC in maize seeds indicating negative relationship of SPC with SOC and SSC. Earlier in sunflower, In Amanullah et al found that seed protein concentration had negative association with seed oil concentration [30]. The SSC decreased and SPC increased with each increment in N supply indicating negative relationship between SSC and SPC [7].…”
Section: Seed Weightmentioning
confidence: 99%
“…The early maturity and higher SOC in maize due to AS application could be due to presence of free S in it that helped the maize plants to achieve early PM and increased SOC. In Amanullah et al found that S fertilized plots might helped the plants to uptake balanced amounts of N and P, and that may have enhanced the plant development and hence early flowering, pod formation, seed fill duration and maturity in Brassica species as compared to the S control plots [30]. Among the maize genotypes, the maize hybrid (P-3025) had delayed PM, increased SPC, SOC, SSC and TSW than the two local cultivars (Azam and Jalal) and was confirmed the most efficient genotype than the two local cultivars because of its positive response to the all three sources and levels of N. Jalal stood second, but Azam because of its early PM, ranked in bottom in terms of its lowest SPC, SOC, SSC and TSW and was considered the least efficient genotype in this study.…”
Section: Seed Weightmentioning
confidence: 99%
“…Currently, increasing attention is being paid to B. juncea worldwide, given its unique and favorable traits, such as resistance to biotic and abiotic stress and a low rate of pod shattering. These traits are desirable in the context of global climate change given its capacity to adapt to heat and other stresses that are commonly encountered under field conditions in Canada, Australia, and many other parts of the world (Woods et al, 1991; Cheung et al, 1997; Burton et al, 2004; Huangfu et al, 2009; Amanullah et al, 2011; Chen et al, 2013). However, genetic improvement on this species is still relatively limited even though previous efforts have significantly increased the yield, particularly increases of seed yield in India (Dr. Zhizheng Chen, personal communication).…”
Section: Introductionmentioning
confidence: 99%